Spatiotemporal heterogeneity and drivers of coupling coordination between agricultural productive services and rice production carbon efficiency: evidence from county-level data in Jiangxi province, China - Wu, Beihe; Gao, Jiangtao; Guo, Yan; Wang, Liguo; Zhao, Haoxiang (Frontiers in Sustainable Food Systems, 2025)
IntroductionAgricultural productive services (APS), as a vital component of modern agricultural industrial systems, play a critical role in advancing green agricultural transformation and sustainable development.MethodsThis study investigates the spatiotemporal evolution, regional disparities, and influencing factors of the coupling coordination degree (CCD) between APS and the carbon efficiency in rice production (RCE) in Jiangxi Province, China. The spatiotemporal patterns, dynamic trends, and driving mechanisms were analysed using kernel density estimation, Dagum Gini coefficient decomposition, and the geographically and temporally weighted regression (GTWR) model.ResultsThe results indicate that the CCD between APS and RCE demonstrates a weakly multipolar dynamic evolution pattern, exhibits an upward trend but remains suboptimal, with significant regional disparities driven by interregional hypervariable density (49.18% contribution). Influencing factors displayed notable spatiotemporal heterogeneity, with contributions ranked as follows: rural population-land scale > financial support for agriculture > planting structure > urban–rural income gap > multiple cropping index > urbanization level.DiscussionOur findings offer insights applicable to Global South countries facing similar challenges in balancing productivity and decarbonization, and we propose actionable strategies to enhance APS systems, establish cross-regional coordination mechanisms, and optimize resource allocation for low-carbon agricultural transitions.